The Islamic World's Perspective on the Development of Modern Science - Syifa Maharani Larasati; Tiara Sekar Harnum; Wafiqotul Adibah; Yusriyyah Febriani Putri; Rizki Amrillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In responding to the dynamic development of modern science, the Islamic worldview has a crucial role that offers unique perspectives and valuable contributions in initiating and shaping the direction of modern knowledge progress. The research aims to see how much the Islamic worldview has influenced modern science. The research focuses on the Islamic concepts, values, and principles that can be found in the development of modern science, as well as how modernization in an Islamic context can proceed in line with religious values. The results show that the Islamic worldview has contributed significantly to the development of modern science, primarily through rationalization that encourages critical thinking and abandoning taqlid in action. Although often associated with modernity, this study asserts that modernization in Islam does not contradict the basic teachings of the religion as long as Islamic values remain the leading guide. The method used in this research is a literature review.